In vivo assessment of mechanical properties during axolotl development and regeneration using confocal Brillouin microscopy - Riquelme-Guzman, Camilo; Beck, Timon; Edwards-Jorquera, Sandra; Schluessler, Raimund; Mueller, Paul; Guck, Jochen; Sandoval-Guzman, Tatiana; Möllmert, Stephanie (Open Biology, 2022)
In processes such as development and regeneration, where large cellular and tissue rearrangements occur, cell fate and behaviour are strongly influenced by tissue mechanics. While most well-established tools probing mechanical properties require an invasive sample preparation, confocal Brillouin microscopy captures mechanical parameters optically with high resolution in a contact-free and label-free fashion. In this work, we took advantage of this tool and the transparency of the highly regenerative axolotl to probe its mechanical properties in vivo for the first time. We mapped the Brillouin frequency shift with high resolution in developing limbs and regenerating digits, the most studied structures in the axolotl. We detected a gradual increase in the cartilage Brillouin frequency shift, suggesting decreasing tissue compressibility during both development and regeneration. Moreover, we were able to correlate such an increase with the regeneration stage, which was undetected with fluorescence microscopy imaging. The present work evidences the potential of Brillouin microscopy to unravel the mechanical changes occurring in vivo in axolotls, setting the basis to apply this technique in the growing field of epimorphic regeneration.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Axolotl; Cartilage; Confocal Brillouin microscopy; Development; Regeneration